Intra Partum Foetal Distress - J Kubheka (AOSIS, 1985)
The occurrence of neonatal asphyxia at Baragwanath Hospital is a daily problem. The question was raised as to whether intra partum foetal distress, apgar scoring at birth and the biochemical analysis of blood acid base status from the chorionic arteries can predict any short-term neurological defects.